Effects of a simulated tennis match on lymphocyte subset measurements - Schafer, M.; Kell, H.; Navalta, J.; Tibana, R.; Lyons, S.; Arnett, S. (Research Quarterly for Exercise and Sport, 2014)
Tennis is an activity requiring both endurance and anaerobic components, which could have immunosuppressive effects postexercise. Purpose: The purpose of this investigation was to determine the effect of a simulated tennis match on apoptotic and migratory markers on lymphocyte subsets. Method: Male high school (n = 5) and college (n = 3) tennis players (M age = 18.9 ± 3.3 years) completed 10 sets of a tennis protocol including serves, forehand strokes, and backhand groundstrokes with 1-min rest periods between sets. Apoptosis antigen 1 receptor (CD95) and chemokine receptor fractalkine (CX3CR1) expression was analyzed on helper T lymphocytes (CD4+), cytotoxic T lymphocytes (CD8+), and B lymphocytes (CD19+) twice, at resting baseline and immediately after all 10 sets of the tennis protocol. Results: An increase was observed in each lymphocyte subtype (p < .02, effect size = .41), and comparison of absolute changes revealed increases in CD4+/CD95+, CD8+/CD95+, and CD8+/CX3CR1 lymphocytes following the tennis protocol (p < .01, effect size = .43), but not in CD19+ cells. Conclusions: A simulated tennis match has adequate intensity to induce immune modulations in terms of increased cell death and cellular migration in T lymphocyte subsets. Lymphocytopenia following tennis play is influenced by both apoptotic and migratory mechanisms.